The Impact of Multinational Enterprises' Spillovers on Indigenous Entrepreneurial Ecosystems - Rizvi, Syed Ali Adnan (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2024)
While the symbiosis of entrepreneurial ecosystems (EE) and large-scale businesses is well-established, the landscape shifts dramatically in contexts where established businesses are scarce. The silver lining? The potential of foreign direct investment (FDI) spillovers to fill this void. Although FDI and entrepreneurship have been extensively discussed, a persistent black box across all agglomeration theories and spillover literature remains: the mechanisms of these MNE spillovers. This gap becomes even more pronounced within the EE literature. Delving into this untapped dimension, our study unravels the intricate relationship between Multinational Enterprises (MNEs) spillovers and the development of native EEs. We steer this exploration through an overarching research question: 'How do MNE spillovers impact the development and evolution of indigenous entrepreneurial ecosystems?'. My first paper stands as a foundational pillar, offering a panoramic view of the spillover literature, zoning in on the elusive mechanisms of MNE spillovers within the EE realm. In doing so, we present a roadmap from MNE entry to spillover mechanics, punctuating the route with untrodden research trajectories. The second paper, enlivened by empirical veracity, focuses on Dublin's EE post-2003?following Google's entry. Despite its monumental transformation, marked by a confluence of global investors, venture capitalists, and unparalleled talent, Dublin's EE narrative remains underrepresented. We aim to bridge this gap, marrying the EE framework with Cantner et al. (2020)'s evolutionary model, offering a vivid portrayal of Dublin's entrepreneurial vibrancy. My culminating paper takes a pragmatic step in unraveling the enigmatic 'black box' of MNE spillover mechanisms. Guided by hypotheses from the inaugural paper, we demystify the intertwined narrative of MNE spillovers and EE evolution, introducing our innovative conceptual tool, FARM. The culmination spotlights uncharted academic avenues, underscoring future research potentials. Collectively, this triadic journey seeks to illuminate the pivotal, yet underappreciated, dynamics between MNE spillovers and entrepreneurial ecosystems, hoping to reshape scholarly discourse and practice alike.
APPROVED
Keywords: spillover; mechanism; MNE; FDI; review; Dublin entrepreneurial ecosystem; Dublin; entrepreneurial ecosystem; FARM